The effects of rapid weight loss on skeletal muscle in judo athletes - Roklicer, R.; Lakicevic, N.; Stajer, V.; Trivic, T.; Bianco, A.; Mani, D.; Milosevic, Z.; Maksimovic, N.; Paoli, A.; Drid, P. (Journal of Translational Medicine, 2020)
Objective: To observe the effect of rapid weight loss (RWL) methods over 3 days on muscle damage in judokas. Methods: Eighteen judokas participated in this crossover study, meaning that judo athletes were subjected to exercise-only phase (4 days) and RWL phase (3 days). Subjects were tested for myoglobin, creatine kinase, aldolase, hemoglobin, and hematocrit values on seven consecutive days. These biomarkers served as indicators of acute muscle damage. Results: During the exercise-only phase, no significant changes were observed. Myoglobin (Mb) (p < 0.001), creatine kinase (CK) (p < 0.001) and aldolase (ALD) (p < 0.001) significantly increased only during the RWL phase, as well as hemoglobin (Hb) (p < 0.001) and hematocrit (Hct) (p < 0.005) values. It was detected that peak values for muscle damage biomarkers were reached on the sixth day, while Hct and Hb values were the highest on the seventh day of the study. Conclusion: Our study showed significant muscle damage induced by RWL. The prevalence of RWL use by judokas is high but firm scientific evidence is lacking in the evaluation of the current practice of it. Therefore, further knowledge must be gained to evaluate the effectiveness of RWL on performance and its impact on judokas` wellbeing.